The Effectiveness of Geographic Information System (GIS) Application in Land Use Planning at Mufulira Municipal Council, Copperbelt Province, Zambia - Peter, Zimba; Enock, Sakala; Beverly, Mushili (IJRDO-Journal of Applied Science, 2017)
This paperexamines the effectiveness of GIS application in land use planning at MufuliraMunicipal Council after the adoption of GIS in 2008.Data was collected using semi-structured questionnaires, recorded interviews, Council GISspatial data and written documents prepared on GIS.Comparative Analysis used to analysecollected data through the process of data documentation, conceptualization, categorizationand examination.Results show that before the adoption of GIS, land use planning in Mufulirawas ineffectivedue to inadequate equipment.GIS implementation has therefore built capacity in themunicipal council to prepare land use layout plans and control development in themunicipality. TheCouncil’splanning department uses GIS on about 75 per cent of its physicalplanning functions.The paper concludes that despite GIS implementation having to some extent improved landuse planning in Mufulira, poor maintenance has negatively affected the operations andexpansion of the GIS unit. It is therefore recommended that the council invests in employingmore GIS personnel, linking the GIS software to all departments of the council and acquiringa GIS server for effective land use planning.